Raphael Lemkin and the Struggle for the Genocide Convention - Cooper, J. author. aut Link
VII, 338 p.
Keywords: This book is the first complete biography of Raphael Lemkin, the father of the United Nations Genocide Convention, based on his papers; and shows how his campaign for an international treaty succeeded. In addition, the book covers Lemkin's inauguration of the historical study of past genocides.